Fire and ice: [a Beaumont and Brady novel] - Jance, Judith A (New York : William Morrow : imprint of HarperCollins, 2009)
Big-city homicide detective J. P. Beaumont and small-town sheriff/mom Joanna Brady join forces once again to solve a case involving a series of murders--six young women wrapped in tarps, doused with gasoline, and set on fire; and one elderly caretaker run over and left to die.
Keywords: Beaumont, J. P. (Fictitious character) -- Fiction; Brady, Joanna (Fictitious character) -- Fiction; Serial murders -- Fiction; Police -- Washington (State) -- Seattle -- Fiction; Sheriffs -- Arizona -- Fiction